How does financial inclusion affect environmental degradation in the six oil exporting countries? The moderating role of information and communication technology - Damrah, Sadeq; Satrovic, Elma; Shawtari, Fekri Ali (Frontiers in Environmental Science, 2022)
Progress in financial inclusion has played a major role in economic development and poverty reduction. However, the environmental impact of financial inclusion calls for urgent implementation of environmental strategies to mitigate climate change. Financial inclusion forces the policies of developed countries to advance and not affect the present and future development of developing countries. Therefore, the current study aims to investigate the direct effects of information and communication technology (ICT) usage on environment as well as its moderating role on the association between financial inclusion and environmental degradation for six oil exporting countries (United Arab Emirates, Saudi Arabia, Russia, Kuwait, Canada, and the United States), using annual panel data from 1995 to 2019. We also analyze the validity of the environmental Kuznets curve (EKC) phenomenon for the entire sample, as well as the role of energy consumption and population. Employing the Method of Moments Quantile Regression (MMQR) with fixed effects, this study supported the existence of EKC phenomenon here as linkage amid human development index and carbon intensity. We find that energy consumption significantly increases carbon intensity. The empirical results showed that the application of internet- and mobile use as indicators of ICT usage lead to environmental preservation in the six oil exporting economies. Also, we observe that financial inclusion has mitigating effects on pollutant emissions, contributing to environmental preservation. Interaction between ICT usage and financial inclusion jointly reduces carbon intensity in all quantile distributions. A robustness check using an alternative proxy of the financial inclusion also confirms that ICT usage significantly and negatively moderates the association between financial inclusion and carbon intensity. Based on the findings of this study, the selected oil exporting countries should integrate financial inclusion with environmental policies to reduce carbon intensity.